RESIDUAL EFFECTS OF INORGANIC FERTILIZER AND BIOCHAR ON LEAD AND CADMIUM UPTAKE BY Amaranthus cruentus L. ON CONTAMINATED SOIL OF BAGEGA, NIGERIA - Victor Odiamehi Onokebhagbe; Kingsley Chinyere Uzoma; Abdu Nafiu; Nkechi Mary Chinke; Ayorinde Ogunsesin; Adeniyi Olarewaju Adeleye (Journal CleanWAS)
The need to remediate contaminated mine soils has led to the adoption of biochar technology. Soils obtained from gold mining sites are heavily contaminated soils due to the presence of heavy metal occlusions in the gold ores. Therefore, a two-trial study was conducted to assess heavy metal uptake by Amaranthus cruentus from biochar amended contaminated mine soils. The experiment was factorial and laid out in a completely randomized design with biochar at seven levels (control; woodchar and bonechar at three rates each) and mineral fertilizer (15-15-15 NPK) at three rates to give rise to twenty-one biochar and fertilizer treatment combinations with three replications. Harvested plant tissues were subjected to wet digestion to determine the concentrations of Pb and Cd. Determined Pb concentrations (0.82-1.04 and 0.74-1.15 mg kg-1) in plant tissues were under the critical limit of 2.0 mg kg-1 set by WHO. Cadmium concentrations (0.38-0.49 and 0.32-0.50 mg kg-1) in plant tissues obtained from both trials were above the critical limit of 0.02 mg kg-1 set by WHO. Values of Pb uptake by plants ranged from 1.99-12.64 mg kg-1 and 0.05-0.71 mg kg-1 in both cropping trials, while Cd uptake ranged from 0.09-0.37 and 0.002- 0.016 mg kg-1. Uptake values of Pb and Cd obtained from the first trial were comparatively higher than values obtained from the second trial. A combination of 30 t ha-1bonechar and 80 kg 15-15-15 NPK enhanced Pb and Cd uptake in both trials while 30 t ha-1 woodchar suppressed heavy metal uptake. Biochar made from plant sources is more suitable for remediating heavy metal contaminated soils.